Near-infrared Spectroscopy-guided Flap Delay: For Flap Training and Timing of Pedicle Division - Sally SJ Chan; Chong H Pek; Yijun Wu; Yuan Kong; Wei M Ho; Jolie JY Hwee (Journal of Plastic and Reconstructive Surgery)
Staged pedicled flaps continue to be a safe and effective technique for reconstructing complex wounds when free tissue transfer is not possible. To induce ischemic preconditioning, serial cross-clamping of the pedicle is performed, which is also known as flap training. Current protocols for flap training are based on arbitrary schedules of progressively increasing periods of ischemia. We describe a simple, safe, and reproducible technique of using near-infrared spectroscopy to objectively guide the process of pedicle cross-clamping and aid in determining the optimal timing for flap division. This technique enables surgeons to adopt a more aggressive clamping schedule based on objective parameters, tailors the clamping schedule to the physiologically tolerable limits of each flap, and allows for early flap division. The principles, feasibility, and advantages of using near-infrared spectroscopy to guide pedicled flap training and early flap division are discussed.